2015
DOI: 10.1121/1.4906832
|View full text |Cite
|
Sign up to set email alerts
|

Auditory, visual, and auditory-visual processing performance in typically developing children: Modality independence versus dependence

Abstract: The study was carried out to determine whether cross-modal interactions occur during processing of auditory and/or visual signals that require separation/closure, integration, and duration pattern perception in typically developing children. Thirty typically developing children were evaluated on three auditory processing tests (speech-in-noise test in Indian-English, dichotic-consonant vowel test, and duration pattern test) that tapped separation/closure, integration and duration pattern perception. The childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Electrophysiological tests have examined the effect of combining auditory-visual information on multi-sensory processing. The results have shown that the scores on recorded tests increased with aging, which is consistent with the current study results [ 14 ]. It has also been shown that children about 6 years old and older can benefit from the integration of auditory-visual sensory for better speech understanding, especially in noisy environments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Electrophysiological tests have examined the effect of combining auditory-visual information on multi-sensory processing. The results have shown that the scores on recorded tests increased with aging, which is consistent with the current study results [ 14 ]. It has also been shown that children about 6 years old and older can benefit from the integration of auditory-visual sensory for better speech understanding, especially in noisy environments.…”
Section: Discussionsupporting
confidence: 93%
“…Auditory-visual multi-sensory processing can be analyzed using an objective method, such as event-related potential (ERP) tests [ 13 ] or through subjective and behavioral tests [ 14 ]. Many studies have been done in the field of electrophysiological tests.…”
Section: Introductionmentioning
confidence: 99%